2021
DOI: 10.1155/2021/6697574
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Promotes Stem Cell Neural Differentiation in Tissue Engineering

Abstract: Nerve injuries and neurodegenerative disorders remain serious challenges, owing to the poor treatment outcomes of in situ neural stem cell regeneration. The most promising treatment for such injuries and disorders is stem cell-based therapies, but there remain obstacles in controlling the differentiation of stem cells into fully functional neuronal cells. Various biochemical and physical approaches have been explored to improve stem cell-based neural tissue engineering, among which electrical stimulation has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 115 publications
0
56
0
Order By: Relevance
“…When implementing in biological systems, the device platform serves a tool to optically and non-genetically interrogate neural activities, with possible utilities in drug screening 74 , brain-machine interfaces 75, 76 and prosthesis 77 . These wirelessly generated electrical signals can also possibly interrogate neurological disorders 78 , guide stem cell migration, modulate progenitor cell development 79, 80 and promote cell growth and regeneration 81, 82 . Additionally, the junction-dependent photovoltage could target electro-sensitive designer cells expressing voltage-dependent receptors for more cell-specific stimulations 83 .…”
Section: Discussionmentioning
confidence: 99%
“…When implementing in biological systems, the device platform serves a tool to optically and non-genetically interrogate neural activities, with possible utilities in drug screening 74 , brain-machine interfaces 75, 76 and prosthesis 77 . These wirelessly generated electrical signals can also possibly interrogate neurological disorders 78 , guide stem cell migration, modulate progenitor cell development 79, 80 and promote cell growth and regeneration 81, 82 . Additionally, the junction-dependent photovoltage could target electro-sensitive designer cells expressing voltage-dependent receptors for more cell-specific stimulations 83 .…”
Section: Discussionmentioning
confidence: 99%
“…ES plays an important role in inducing appropriate stem cell responses and has great potential to modulate stem cell proliferation, self-renewal, and differentiation. Recent studies have confirmed that the differentiation of cultured NSCs into neurons is directly related to the regulation of ES (Cheng et al, 2021). ES may be directly involved in the up-regulated expression of L-type voltage-gated calcium channels (L-VGCCs), which are essential for the activation of Ca 2+ -dependent pathways through Ca 2+ influx (Wu et al, 2019).…”
Section: Collagen/polypyrrole40 Coupled Es To Promote Neural Stem Cel...mentioning
confidence: 99%
“…Taking advantage of this leakage currents as well as the intrinsic high e ciency of hydrogel in ionic transport with biological tissue, this LM-hydrogel hybrid here can be used as electrical stimulation electrode with safe, wet and biocompatible hydrogel interface. In this section, we demonstrate the capacity of this hybrid for in vitro electrical stimulation of cells, which is of great value in tissue engineering 28,29 , neural regeneration 30,31 and other medical therapy 32,33 . Fig.…”
Section: In Vitro Electrical Stimulation Of Muscle Cellsmentioning
confidence: 99%